What Works in a Commercial: Measuring Effective Frequency within a 30 second commercial - Bramwell, Nathan (Missouri Southern State University (Joplin, Mo.), 2012)
Summary: The research project collects and analyzes data to "determine how prevalent effective frequency, commercial type and product/brand familiarity had on the recall ability of each commercial"--p. 3.; 39 pages : PDF file ; cm.